Coronary artery aneurysm formation after paclitaxel-coated balloon-only intervention for de novo coronary chronic total occlusion - Jun, Eun Jung; Shin, Eun-Seok; Kim, Bitna; Teoh, Eu-Vin; Chu, Chong-Mow; Kim, Sunwon; Liew, Houng Bang (Frontiers in Cardiovascular Medicine, 2023)
Background Although coronary artery aneurysm (CAA) is an uncommon complication of drug-coated balloon (DCB) treatment, the incidence and mechanisms CAA formation after DCB intervention for chronic total occlusion (CTO) remains to be clarified. The aim of this study was to investigate the incidence of CAA after DCB intervention for the treatment of CTO of coronary arteries. Materials and methods This was a retrospective analysis of 82 patients, contributing 88 vessels, who underwent successful DCB-only treatment for de novo CTO lesions. Follow-up angiography was performed in all cases, at a mean 208.5 (interquartile range [IQR]: 174.8 to 337.5) days after the index procedure. Results CAA was identified in seven vessels, in seven patients, at the site of previous successful DCB-only treatment. Of these, six were fusiform in shape and one saccular, with a mean diameter of 4.2 ± 1.0 mm and length of 6.7 ± 2.6 mm. Six CAAs developed at the CTO inlet site, and all CAAs occurred at the lesions following dissection immediately after DCB treatment. CAAs were not associated with an increased risk of major clinical events over the median follow-up of 676.5 (IQR: 393.8 to 1,304.8) days. Conclusion The incidence of CAA after DCB-only treatment for CTO lesions was 8.0% in this study. Further research is warranted, using intravascular imaging, to clarify the mechanism of DCB-related CAA formation and prognosis.